A room with a view: a metaphor analysis of Vietnamese women's representations of living with depression using photo elicitation. Issue 3 (3rd July 2018) - Palmer, Victoria Jane; Furler, John
Abstract : Depression is complex and it is known that how people name and give meaning to this experience when they are from cross cultural backgrounds differs to that of dominant Anglo cultures. Yet surprisingly very little is known about the naming and meaning-making conventions particularly for Vietnamese communities. In Anglo cultures, people commonly describe their experiences of depression as 'travelling through dark tunnels toward a light'; 'climbing out of a hole'; 'a black dog', and the 'descent of a black cloud'. These metaphoric representations provide us with visual messages and new meanings about the experience of depression and how it impacts individuals. In this article, we describe a study that aimed to examine if a photo elicitation method could provide a group of women from Vietnamese backgrounds with another language set by which to represent their experience of depression in the face-to-face interview context. Women were provided with a digital camera and asked to take a minimum of 10 photos about their everyday experiences of living with depression. Recruitment and face-to-face interviews were completed with an interpreter already known to participants employed at the community health centre. Participants were asked to select five key photos for discussion within the interpreted interview. In the following article, a metaphor analysis is presented to reflect on how the photos enabled further insight into Vietnamese women's representations of living with depression and examine the application of this participatory visual method for cross cultural research settings.